An assessment on S&T careers leading to technology creation - Esquivel, Susana F. (University of the Philippines Diliman, 2010)
The Department of Science and Technology through the Science Education Institute (DOST-SEI) which implements various undergraduate scholarship programs in the country is continuing its efforts to attain the status of a Newly Industrializing Country (NIC). Since 1958 the scholarship programs produced a lot of scholar-graduates who are now in their respective fields in the industry. However, despite its aim to ensure a steady, adequate supply of qualified S&T human resources which can steer the country towards national progress, there are scholars who work abroad to find greener pasture. There are also those who graduated but to date did not report about their employment status. Thus, the number of human resources decreases and its accumulation from the time the scholarship programs started is a big deduction on what they can contribute to the country. The outcome of the study revealed that the DOST-SEI has a great impact in providing the RA7687 Scholarship Program to deserving and talented students with high aptitude in science and mathematics. The basic criteria of eligibility, i.e. the student must belong to the upper 5 percent of the graduating class is truly an effective strategy of the lawmakers to get the cream dela cream among students who can steer the country towards national progress. The implementation scheme of the program is already established. However, the government has no specific strategy yet on how these scholars will be deployed accordingly. The DOST-SEI has no strong linkage with the industries that will lead these scholars to develop their undergraduate training. The quality of education that SUCs provided will not be meaningful if these scholars will not be placed according to their fields of specialization. Advanced countries are spending a lot not only in producing human resources but more importantly in R&D which is the key to becoming independent scientifically and technologically. This is another major area that the government should work on by providing a big portion of the national budget in R&D.